2021
DOI: 10.14283/jfa.2021.43
|View full text |Cite
|
Sign up to set email alerts
|

Social Frailty and Executive Function: Association with Geriatric Syndromes, Life Space and Quality of Life in Healthy Community-Dwelling Older Adults

Abstract: Background: Despite emerging evidence about the association between social frailty and cognitive impairment, little is known about the role of executive function in this interplay, and whether the co-existence of social frailty and cognitive impairment predisposes to adverse health outcomes in healthy community-dwelling older adults. Objectives: We aim to examine independent associations between social frailty with the MMSE and FAB, and to determine if having both social frailty and cognitive impairment is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Previous studies have shown that this correlation is often high, as individuals with FTD often show signs of general cognitive impairment (Goh et al, 2019;Slachevsky et al, 2004). Furthermore, the impact of cognitive reserve on cognitive function has been highlighted in both individuals at risk for FTD and those without, which adds novelty to our findings (Ong et al, 2021;Coen et al, 2016). Despite limitations, the inclusion of the effect of cognitive reserve in our analysis enriches an understanding of its role in different clinical contexts (Pellas & Damberg, 2024;Woodford & George, 2007).…”
Section: Limitations and Directions For Further Researchmentioning
confidence: 70%
“…Previous studies have shown that this correlation is often high, as individuals with FTD often show signs of general cognitive impairment (Goh et al, 2019;Slachevsky et al, 2004). Furthermore, the impact of cognitive reserve on cognitive function has been highlighted in both individuals at risk for FTD and those without, which adds novelty to our findings (Ong et al, 2021;Coen et al, 2016). Despite limitations, the inclusion of the effect of cognitive reserve in our analysis enriches an understanding of its role in different clinical contexts (Pellas & Damberg, 2024;Woodford & George, 2007).…”
Section: Limitations and Directions For Further Researchmentioning
confidence: 70%
“…The executive function is a higher-level function of the verbal fluency task [ 28 ] and is recognized as one of the key factors associated with the ability to set goals, make plans, modify and adjust while actually performing the actions, and carrying out effective actions in everyday life [ 29 ]. Thus, it is related to the ability of daily living/instrumental activities of daily living (ADL/IADLs) [ 30 , 31 ], social frailty [ 32 ] and importantly, life satisfaction [ 33 ] for older adults. In fact, such a simple verbal fluency task has a rather complex mechanism, as many cognitive functions are interrelated during this task, including semantic memory, dialectical lexical retrieval, information processing speed, inhibition, working memory, shifting performance and cognitive flexibility [ 29 ], and it includes a variety of anatomical sites.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty can occur due to adverse health outcomes, including physical conditions (e.g., heart failure), psychological conditions (e.g., cognitive impairment), and social conditions (e.g., isolation) [ 6 ]. The consequences of frailty in older adults include reduced motor function [ 7 ], falls [ 8 ], mental disorders [ 9 ], increased hospitalization rates [ 10 ], and death [ 11 , 12 ]. Frailty is a multidimensional concept that encompasses physical, mental, and social dimensions [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SFS-8 assesses social frailty using eight items and three dimensions, including social resources, social activities and financial resources, and fulfillment of social needs [ 22 ]. The SFS-8 has been used in many studies, especially in Asian countries [ 12 , 13 , 24 ].…”
Section: Introductionmentioning
confidence: 99%